Optimizing Teachers’ HOTS Assessment Competence in Maritime-Based Schools Through Structured Training Intervention - Sarkity, Dios; Fernando, Adam; Pratama, Yudi; Intasir, M. Pemberdi; Yunus, Muhammad (Universitas Lambung Mangkurat, 2026)
This community service program aimed to improve teachers’ competence in developing Higher Order Thinking Skills (HOTS)-based assessment items integrated with maritime contexts at SMPN 11 Tanjungpinang. The program employed a Participatory Action Research (PAR) approach, emphasizing collaborative problem identification, action, and reflection to ensure alignment with teachers’ real instructional needs. The participants consisted of 24 teachers from various subject areas at a maritime-based junior high school in the Riau Islands. The program was implemented through three structured stages: (1) a needs analysis conducted through interviews and focused group discussions to identify challenges in HOTS-based assessment, (2) a training phase involving conceptual reinforcement of HOTS and 21st-century skills, guided practice in constructing C4–C6 assessment items using maritime-based stimuli, and collaborative review, and (3) a post-implementation stage focusing on evaluation and reflection. Program outcomes were evaluated using pre- and post-tests, a rubric-based HOTS item development task, and a participant satisfaction questionnaire. The results indicated a significant improvement in teachers’ conceptual understanding, with a high N-Gain score (0.76) in the introductory module and moderate gains in subsequent technical modules. Teachers successfully produced high-quality HOTS assessment items that demonstrated strong alignment between learning objectives, cognitive levels, and maritime contextual relevance. Participant responses showed very high satisfaction (93.24%), indicating that the program was relevant, practical, and beneficial for professional development. In conclusion, the PAR-based structured training had a positive impact on strengthening teachers’ HOTS assessment competence in a maritime-based school context. The program also contributed to increased readiness for sustainable implementation of contextualized HOTS-oriented assessment practices, highlighting the importance of continued mentoring and follow-up support.